Influence of Different Fiber Materials on the Performance of Concrete Segment Joints - ZHOU Chunxu; ZHAO Licai; ZHU Jungao (Chengshi guidao jiaotong yanjiu)
［Objective］Due to their low tensile strength and poor impact resistance, ordinary concrete segments are prone to problems such as cracking and deformation during the transportation and construction process. Adding fibers is an effective way to prevent and control these defects. Therefore, it is necessary to study the effects of different fiber materials on the performance of concrete segment joints. ［Method］Through indoor tests, concrete segments containing steel fibers, polypropylene fibers and two types of mixed fibers are designed, and compared with ordinary concrete segments without admixtures, so as to analyze the effects of different types and dosages of admixtures on compression, bending and pull-out properties at concrete segment joints. On the basis of determining the optimal admixture materials, the effects of different admixture dosages on the mechanical properties of concrete segment joints are studied. ［Result & Conclusion］The addition of fibers can effectively prevent the crack development at concrete segment joints, among which the concrete with mixed fibers has the most obvious improvement on the overall performance of the concrete segment joints. The greater the fiber dosage, the more effective it is in preventing crack development at the joints. From the perspective of the crack development characteristics of the segments, with the addition of fibers, almost no visible development of penetrating cracks. The greater the fiber dosage, the more obvious this improvement is in crack development .